Robust interfacial network and ionic conduction of carbon-doped hexagonal boron nitride for dual-mode strain and humidity sensor - Muhammad Mujtaba Syed; Balamurugan Thirumalraj; Abdallah Kamal; Baosong Li; Dezhuang Ji; Dawei Zhang; Muhammad Umair Khan; Baker Mohammad; Kin Liao; Lianxi Zheng (Chemical Engineering Journal, 2026)

Flavonoids as colchicine binding site inhibitors: emerging scaffolds in anticancer drug design - Ahmed Maebed; Yuhanis Mhd Bakri; Yasser M. Omar; Saripah Salbiah Syed Abdul Azziz; Abu-Baker M. Abdel-Aal (Medicinal Chemistry Research, 2026)

Structural characterization and metabolomic insights of biofunctional nanoparticles synthesized from Curcuma caesia Roxb - Lakshmi S; Vaibhavi J Godkhindi; Spoorthi S; Sudeep D; Aryaa N Murthy; Nagendra Prasad M N; Raj Niranjan S; Manju K; Syed Baker (Next Research, 2025)

Correction: Aspergillus niger TC1 as multi-functional bioinoculant for biodegradation of chlorpyrifos, plant growth promotion and biocontrol of phytopathogens - Purushotham Tejashwini; Javaraiah Parashiva; Chandagalu Ramesh Santhosh; Syed Baker; Sreedharamurthy Satish (Biodegradation, 2025)

Sustainable biodegradation of chlorpyrifos by microorganisms: a review - Purushotham Tejashwini; Syed Baker; Javaraiah Parashiva; C. R. Santhosh; B. P. Harini; S. Niranjan Raj; S. Satish (Vegetos, 2025)

AI-enabled smart bioengineering for sustainability - Shayista H; Lakshmi Kalyani Chinthala; Kshithij G Raj; Akshatha P; Niranjan Raj S; Manju K; Ravi Kumara; Lakshmi S; Roopanjanli S; Vaibhavi J Godkhindi; Pratheeksha M C; Nagendra Prasad M N; et al. (Next Research, 2025)

Aspergillus niger TC1 as multi-functional bioinoculant for biodegradation of chlorpyrifos, plant growth promotion and biocontrol of phytopathogens - Purushotham Tejashwini; Javaraiah Parashiva; Chandagalu Ramesh Santhosh; Syed Baker; Sreedharamurthy Satish (Biodegradation, 2025)

Nanoparticle embedded cellulosic film: Synergistic influence on antibacterial activity and sustainable agronomic evaluation - Syed Baker; Svetlana V. Prudnikova; Anna A. Sukhanova; Olga V. Perianova; Niranjan Raj S; Chandra Nayaka S; Tatyana A. Garkusha; Ivan P. Shidlovskiy; Nadezhda K.Potkina; Olga Y. Khohlova; Andrey Kuzmin; Manju K; et al. (Biocatalysis and Agricultural Biotechnology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Role of fruit volatiles of different guava varieties in attraction and oviposition behaviors of peach fruit fly, Bactrocera zonata Saunders - Muhammad Binyameen; Abdul Hamid; Imran Afzal; Muhammad Sajjad; Muhammad Azeem; Syed Muhammad Zaka; Zahid Mehmood Sarwar; Sarfraz Ali Shad; Thomas C. Baker; Fredrik Schlyter (Arthropod-Plant Interactions, 2021)